Community Problem-Based Learning Activities to Raise Awareness of Environmental Issues Among Primary School Grade 5 Students in Ban Na Klam Community - Janoun, Nantawad; Pooncharoen, Nattachet (Journal of Buddhist Education and Research (JBER), 2025)
This qualitative study aimed to 1) to study the environment in Ban Naklam community, Nam Khrai sub-district, Nam Pat district, Uttaradit province at present, and 2) to develop learning management activities to raise environmental problem awareness using community problems as a base for primary 5 students in Ban Naklam community. The informants consisted of 1) 3 experienced geography teachers, 2) 2 representatives from government agencies and community leaders, 3) 15 target students. The study area was Chumchonbannaklam School. The research instruments consisted of 1) interview questions about the environment in the study area and learning management in geography, 2) observation record form. The data were analyzed by content analysis and descriptive synthesis. The research results found that the study area is experiencing environmental degradation, high temperatures during the dry season, reduction of trees due to forest burning, and smog which affected. The interviews revealed that: The informants agreed to organize a geography learning activity under the topic “Protecting the Forest, Starting with Us” which consisted of 4 activities: 1) Finding the Cause, Solving the Mystery of Forest Fires 2) Exploring, Finding Forest Fire Risk Points 3) Protecting the Forest, Preventing Fires 4) Forest Protection Heroes. These activities helped to increase students’ awareness of the forest fire problem and its impact on the environment in the community.